PHENOTYPIC CHARACTERISTICS OF ROD–CONE DYSTROPHY ASSOCIATED WITH MYO7A MUTATIONS IN A LARGE FRENCH COHORT. Issue 8 (August 2020) - Khateb, Samer; Mohand-Saïd, Saddek; Nassisi, Marco; Bonnet, Crystel; Roux, Anne-Françoise; Andrieu, Camille; Antonio, Aline; Condroyer, Christel; Zeitz, Christina; Devisme, Céline; Loundon, Natalie; Marlin, Sandrine; et al.
Abstract : Purpose: To document the rod–cone dystrophy phenotype of patients with Usher syndrome type 1 (USH1) harboring MYO7A mutations. Methods: Retrospective cohort study of 53 patients (42 families) with biallelic MYO7A mutations who underwent comprehensive examination, including functional visual tests and multimodal retinal imaging. Genetic analysis was performed either using a multiplex amplicon panel or through direct sequencing. Data were analyzed with IBM SPSS Statistics software v. 21.0. Results: Fifty different genetic variations including 4 novel were identified. Most patients showed a typical rod–cone dystrophy phenotype, with best-corrected visual acuity and central visual field deteriorating linearly with age. At age 29, binocular visual field demonstrated an average preservation of 50 central degrees, constricting by 50% within 5 years. Structural changes based on spectral domain optical coherence tomography, short wavelength autofluorescence, and near-infrared autofluorescence measurements did not however correlate with age. Our study revealed a higher percentage of epiretinal membranes and cystoid macular edema in patients with MYO7A mutations compared with rod–cone dystrophy patients with other mutations. Subgroup analyses did not reveal substantial genotype–phenotype correlations. Conclusion: To the best of our knowledge, this is the largest French cohort of patients with MYO7A mutations reported to date. Functional visual characteristics of this subset of patients followed a linear decline as in other typical rod–cone dystrophy, but structural changes were variable indicating the need for a case-by-case evaluation for prognostic prediction and choice of potential therapies. Abstract : Supplemental Digital Content is Available in the Text.We undertook genetic and phenotypic analysis of 53 MYO7A French patients with Usher syndrome type 1. We identified 50 different genetic variations of which 4 are novel. A linear pattern of visual function deterioration with age was revealed by longitudinal assessment of functional retinal data rather than by multimodal imaging parameters.